Activation of aryl hydrocarbon receptor (AhR) in mesenchymal stem cells modulates macrophage polarization in asthma. Issue 1 (1st January 2020) - Cui, Zhuang; Feng, Yuan; Li, Danqing; Li, Taoping; Gao, Peisong; Xu, Ting
Abstract: Macrophage polarization has been demonstrated to exert a vital role on asthma pathogenesis. Mesenchymal stem cells (MSC) have the capacity to modulate macrophage differentiation from a pro-inflammatory M1 phenotype toward an anti-inflammatory M2 phenotype. However, the impact of MSC-macrophage interactions on asthma development and underlying mechanisms responsible for this interaction remain largely unknown. The aim of this study was to investigate the role of AhR expressed on MSC in macrophage polarization in a cockroach extract (CRE)-induced asthma mouse model. The studies here revealed that MSC polarized macrophages from a pro-inflammatory M1 phenotype toward an anti-inflammatory M2 phenotype in this model. The mRNA levels of interleukin (IL)-6, IL-1β, and NOS2 as M1 markers were significantly decreased while those of select M2 markers such as Arg-1, FIZZ1, and YM-1 were significantly enhanced. It was also observed that aryl hydrocarbon receptor (AhR) signaling was significantly increased during asthma pathogenesis as demonstrated by enhanced mRNA expression of AhR, CYP1a1, and CYP1b1. It was also seen that the elevated AhR signaling was able to attenuate the onset of asthma. Use of an AhR antagonist (CH223191) resulted in significant inhibition of the AhR signaling and increases in M2 marker expression, but led to elevation of expression of M1 markers in the CRE-induced asthma model. Taken together, the current study showed that MSC can modulate macrophage polarization, in part, via activation of AhR signaling during CRE-induced asthma.